A Cross-cultural Study of The Speech Act of Compliments in American English and Yemeni Arabic - Najeeb Taher Almansoob; Yasser Alrefaee; K.S Patil (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
Based on a cross-cultural perspective, the current study aims to compare the realization of the speech act of compliments among Yemeni Arabic native speakers (YANSs) and American English native speakers (AENSs). Samples of 30 participants of Americans and 30 other participants of Yemenis were involved in the study. The data were collected through a Discourse Completion Test (DCT) consisting of six hypothetical compliment scenarios. The corpus collected for analysis was 380 Arabic compliment semantic formulas and 338 English compliment semantic formulas. Data were analyzed in terms of frequency counts of 20 strategies and order of semantic formulas in the speakers' response utterances. The findings showed that there are some pragmatic similarities and differences between the two native groups. Some strategies seemed to be universal across the two cultures like Admiration whereas strategies of Exaggeration, Gratitude to God and Metaphor are culturally specific to Arabic. The findings also revealed that most of the speakers' utterances were in the two-fold order of semantic formulas. Moreover, the findings showed that American compliments were steady and formulaic in nature while Arabic Compliments were various in formulas and long.